Congenital hyperinsulinism: 2 case reports with different rare variants in ABCC8 - Julie Mouron-Hryciuk; Sophie Stoppa-Vaucher; Kanetee Busiah; Thérèse Bouthors; Maria Christina Antoniou; Eric Jacot; Klaus Brusgaard; Henrik Thybo Christesen; Khalid Hussain; Andrew Dwyer; Matthias Roth-Kleiner; Michael Hauschild (Korean Society of Pediatric Endocrinology, 2021)
Congenital hyperinsulinism (CHI) is a rare glucose metabolism disorder characterized by unregulated secretion of insulin that leads to hyperinsulinemic hypoglycemia (HH). Most cases are caused by mutations in the KATP-channel genes ABCC8 and KCNJ11. We report 2 patients that experienced severe HH from the first day of life. Patient 1 developed midgut volvulus after initiating diazoxide and required intestinal resection. He was subsequently managed with a high-dose octreotide and glucose-enriched diet. Consistent with diffuse type CHI by 18F-dihydroxyphenylalanine positron emission tomography-computed tomography, genetic testing revealed a homozygous ABCC8 variant, c.1801G>A, p.(Val601Ile). The rare variant was previously reported to be diazoxide-responsive, and the patient responded well to diazoxide monotherapy, with clinical remission at 2 years of age. Patient 2 responded to diazoxide with spontaneous clinical remission at 15 months of age. However, an oral glucose tolerance test at 7 years of age revealed hyperinsulinism. Genetic testing revealed that the proband and several seemingly healthy family members harbored a novel, heterozygous ABCC8 variant, c.1780T>C, p.(Ser594Pro). Genetic findings identified previously unrecognized HH in the proband's mother. The proband's uncle had been diagnosed with monogenic ABCC8-diabetes and was successfully transitioned from insulin to glibenclamide therapy. We report findings of intestinal malrotation and volvulus occurring 2 days after initiation of diazoxide treatment. We also report a novel, heterozygous ABCC8 variant in a family that exhibited cases of CHI in infancy and HH and monogenic diabetes in adult members. The cases demonstrate the importance and clinical utility of genetic analyses for informing and guiding treatment and care.